Accuracy Evaluation and Modification Method for Estimating Point Light Spot Positions with Gaussian Fitting Algorithm. Issue 1 (January 2021) - Mao, Shuai; Shen, Jin; Wang, Yajing
Abstract: This paper presents an accuracy evaluation method for point light spot position estimation with a Gaussian fitting algorithm combined with a centroid algorithm. Using centroid algorithm in the region around the Gaussian fitting distribution position estimation gets a position estimation value, and it is found that the deviation between this value and the Gaussian fitting algorithm position estimation approximately indicates the deviation between the Gaussian fitting algorithm position estimation and the real one. And at the basis of this finding, a modification method is proposed for position estimation with the Gaussian fitting algorithm. Experimental results show that the accuracy evaluation errors are less than 0.62 nm for 100- and 500-nm diameter fluorescent nanospheres, and the proposed modification method can enhance the accuracy by 3.1 nm.